Lingkar Lengan Atas Dan Kadar Haemoglobin Terhadap Status Gisi Mahasiswi Tingkat 1 Prodi D.III Kebidanan Poltekkes Manado - Purwandari, Atik; Tombokan, Sandra GJ; Adam, Yulien; Fajrin, Irmashanti; Lontaan, Anita; Korompis, Martha Debora; Dompas, Robin; Tuju, Sjenny Olga; Novitasari, Anis (JIDAN Jurnal Ilmiah Bidan, 2024)
Background: The prevalence of anemia in teenagers is 32%, meaning that 3-4 out of 10 teenagers suffer from anemia. This is influenced by suboptimal nutritional intake habits, inappropriate food choices and lack of physical activity.. Objective: This research is to identify LILA, HB Levels and Nutritional Status of Level 1 Students of the D3 Midwifery Study Program, Manado Health Polytechnic. Method: This research is quantitative research using a cross sectional design. The research population was Diploma III Midwifery Study Program students with a total research sample of 60 people. Sampling was carried out using a purposive sampling technique with inclusion criteria, namely that young women had menstruated and were willing to become research subjects by signing informed consent. The data was analyzed using the Chi-Square statistical test. Results: there are more respondents with Normal LILA than those with KEK, HB levels are mostly normal. And the nutritional status of students based on BMI measurements is mostly normal, but there are still students with nutritional disorders. Statistical tests show that there is a relationship between KEK and the nutritional status of young women, there is no relationship between HB levels and nutritional status in teenagers. Recommendations for young women to consume food with balanced nutrition to meet nutritional requirements so that they can avoid CED and consume blood supplement tablets to avoid anemia, according to the Government program. Young Women take 1 Fe tablet once a week for 1 year.